Pengaruh Progressive Muscle Relaxation Dengan Pursed Lips Breathing Terhadap Fatigue dan Depresi - Danismaya, Irawan (PT. Alahyan Publisher Sukabumi, 2024)
COPD is one of the chronic diseases that can cause fatigue, depression and respiratory system disorders. One of the efforts to overcome anxiety and depression in similar chronic diseases to reduce fatigue is by using the Progressive Muscle Relaxation (PMR) method. Another effort to increase the oxygen supply to the alveoli is through breathing exercises, one of which is Pursed Lips Breathing (PLB). Objective: To analyze the relationship between progressive muscle relaxation and purshed lips breathing on Depression Score, Fatigue Score and respiratory function in COPD patients. Research Design: Quantitative research, with experimental design through the pretest-posttest randomized control group design approach. In the experimental study, random assignment was carried out into groups where the researcher made a comparison between the intervention group and the control group. Sampling technique by Consercutive sampling. Data collection using the FACIT-T, BDI II questionnaire, was analyzed using paired t-tests. Results: There was an effect of progressive muscle relaxation with pursed lips breathing on the decrease in fatigue score and depression score with a p value of 0.000 while for respiratory function there was no effect with a p value of 0.191. Suggestion: PMR with PLB can be used as one of the interventions in treatment to prevent fatigue and depression taught to COPD patients during control in the pulmonary polyclinic room which can be used as a preventive measure and as one of the interventions in discharge planning for patients who will go home in the inpatient room.